MODEL-MODEL PENYELENGGARAAN UNIT PRODUSKI DI SEKOLAH MENENGAH KEJURUAN (SMK) DAERAH ISTIMEWA YOGYAKARTA - Martubi Martubi (Universitas Negeri Yogyakarta, 1999)
Abstract The purpose of this study is to portray the implementation and models of production units as partial characteristics of vocational high school in Yogyakarta Special Territory. The study is descriptive in nature, using documentation, questionnaire and interviews supplemented by casual observations involving five vocational high schools specializing in industrial and technological programs. The data was analyzed using both quantitative and qualitative methods. The study concludes that the concept of production units is not widely understood, needs more intensive socialization and more rigorous planning. The program has many constrains to overcome, especially in human resources factor. Prominent types of business found in school production units include manufacturing and maintenance service, applying both regular and contract system. Keywords: vocational schools, production units, educational relevance